Antifungal Activity and Chemical Composition of Thyme, Peppermint and Citronella Oils in Vapor Phase against Avocado and Peach Postharvest Pathogens. Issue 1 (8th February 2013) - Sellamuthu, Periyar Selvam; Sivakumar, Dharini; Soundy, Puffy
Abstract The antifungal activity of three essential oils thyme: (Thymus vulgaris L), peppermint, (Mentha piperita L) and citronella (Cymbopogen nardus); against two avocado postharvest fungal pathogens: Colletotrichum gloeosporioides (anthracnose), Lasiodiplodia theobromae (stem‐end rot); and three peach pathogens: Monilinia fructicola (brown rot), Rhizopus stolonifer (Rhizopus rot) and Penicillium expensum (blue mould rot), was assayed using a disc volatilization method. In vitro study revealed that in the vapor phase, thyme oil at 5 μL/plate as opposed to peppermint and citronella oils completely inhibited the radial mycelia growth of all five pathogens. gas chromatograph/mass spectrometry analysis showed thymol (58.77%), menthol (46.45%) and R (+) citronellal (27.59%) as the major compounds in thyme, peppermint and citronella oils, respectively. Thyme oil vapor showed a fungicidal effect on C. gloeosporioides, L. theobromae and R. stolonifer at 5 μL/plate. Thyme oil vapor at 66.7 μL/L significantly reduced anthracnose and stem‐end rot in artificially wounded and infected fruit. Therefore, these results suggest that thyme oil vapors could be used as alternate natural fungicide to control the common postharvest diseases in avocado. Practical Applications Growers and suppliers of fresh produce are faced with the challenge of providing consumers with products that are attractive, free from disease, defects and toxic residues, and with longer shelf or storage life. The strict regulations enforced by the fresh produce‐importing countries regarding the minimum pesticide residue levels in the edible portion of the fresh produce, increasing resistance to synthetic fungicides by fungal pathogens, waste disposal of fungicides and growing concerns to lower the associated environmental footprint have necessitated the search for a natural novel fungicide to replace synthetic fungicide applications in the packing line as postharvest treatment. Consumer preference to organic fresh produce is increasingly becoming popular in developed countries. On the other hand, synthetic fungicide applications are expensive for small‐scale farmers from developing countries. Therefore, considering all the reasons mentioned earlier, the results of our study provide a novel practical tool using thyme oil vapors to reduce losses because of postharvest diseases in avocado, and thus ensuring safe food.